Elementary Mathematics Learning Devices with Scientific Approach Based on Process Skills - Iwan Usma Wardani (Budapest International Research and Critics University, 2022)
This study aims to describe the steps for developing elementary mathematics learning tools with a process skills-based scientific approach to improve mathematics learning outcomes and to describe the quality of the development tools. The quality of the development results is determined based on the criteria of Nieveen, namely valid, practical and effective. The competencies used in the development are Class VI statistical competencies. This research is a development research. The learning device development model in this study was adapted from the ADDIE model development model which consists of analyze, design, develop, implementation and evaluation stages. The trial was carried out in three stages, namely (1) trial / expert validation; (2) limited trials; and (3) field trials. Field trials were carried out at MI Hamzanwadi No. 1 Pancor. The research instruments used were RPP assessment sheets, LKPD assessment sheets, student response questionnaires, teacher response questionnaires and learning implementation observation sheets. The validity data analysis and the practicality data analysis were each carried out by converting the quantitative data in the form of the assessment results into qualitative data in the form of a standard scale of five. The data analysis of the effectiveness of the competency achievement test was carried out by determining the minimum percentage of completeness. This study produced learning tools consisting of lesson plans with 4 meetings, 4 subchapter student activity sheets (LKPD), and mathematics learning outcomes tests on statistical competence. Each component of the learning device is valid, practical, and effective